Rare Isotope Production in peripheral heavy-ion collisions in the energy range 15-25 MeV/nucleon - Papageorgiou, A.; Souliotis, G. A.; Kwon, Y. K.; Tshoo, K.; Jeong, S. C.; Veselsky, M.; Bonasera, A. (HNPS Advances in Nuclear Physics, 2019)
In this contribution we summarize recent efforts to describe the production of rare isotopes with beams of 15–25 MeV/nucleon expected from low-energy facilities. We first present calculated production cross sections of proton-rich nuclides from collisions of stable beams of mass A∼60–80. Our calculations are performed with the phenomenological deep-inelastic transfer (DIT) model and the microscopic con- strained molecular dynamics model (CoMD). De-excitation of the excited quasipro- jectiles from the dynamical stage of the reaction is performed with the statistical multifragmentation model (SMM). In addition to the efforts on proton-rich nuclides, we investigated the possibility of producing neutron-rich rare isotopes in the mass range A∼180–200, i.e. near the third r-process peak of A=195. We performed calcu- lations for a 208Pb (15MeV/nucleon) beam and find that the multinucleon transfer mechanism leads to very neutron-rich nuclides in this mass range. We believe that our continued progress on the study of multinucleon transfer reactions using heavy- ion beams of 15–25 MeV/nucleon, can provide new opportunities in rare isotope research in the near future, as planned at the KOBRA facility of RISP in Korea.